High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Using recent genetic history to inform conservation options of two Lesser Caymans iguana (Cyclura nubila caymanensis) populations - Thea F. Rogers; Ewan H. Stenhouse; Hannah Wilson; Morgan Pendaries; Michael W. Bruford; Matthias Goetz; Pablo Orozco-terWengel (Conservation Genetics, 2024)
The Sister Islands rock iguana ( Cyclura nubila caymanensis ) is critically endangered and endemic to the Caribbean islands Little Cayman and Cayman Brac. The Cayman Brac population and indeed the entire species is under threat from habitat destruction, invasive species, and anthropogenic impacts on the island. We assessed the genetic diversity, estimated effective population sizes, and tested for differentiation of populations between these two islands to inform potential future translocation should this be needed for the Cayman Brac population. Two mitochondrial DNA markers (cytochrome b and NADH subunit 4) and seven DNA microsatellite markers were used to assess the genetic diversity, genetic structure, demographic history, and effective population size of the two iguana populations. Mitochondrial DNA showed no genetic differentiation between populations; however, we found little to moderate divergence with microsatellites. We compared multiple demographic scenarios and revealed that ongoing gene flow is likely. The demographic history implied a significant genetic bottleneck around 10,000 years ago, coinciding with the sea level rise at the close of the last glacial period, and the start of the Holocene. Estimates of current effective population sizes indicate a small-scale number of breeders on each island of similar magnitude to the census mature population size (between 100 and 800 individuals). The relatively low differentiation between populations supports the possible development of active genetic management plans to manage the declining populations of the Sister Islands rock iguana.

Shifts in Ecological Legacies Support Hysteresis of Stand Type Conversions in Boreal Forests - X. J. Walker; K. Okano; L. T. Berner; R. Massey; S. J. Goetz; J. F. Johnstone; M. C. Mack (Ecosystems, 2023)

Distinct patterns of inheritance shape life‐history traits in steelhead trout - Anne K. Beulke; Alicia Abadía‐Cardoso; Devon E. Pearse; Laura C. Goetz; Neil F. Thompson; Eric C. Anderson; John Carlos Garza (Molecular Ecology, 2023)
Life‐history variation is the raw material of adaptation, and understanding its genetic and environmental underpinnings is key to designing effective conservation strategies. We used large‐scale genetic pedigree reconstruction of anadromous steelhead trout ( Oncorhynchus mykiss ) from the Russian River, CA, USA, to elucidate sex‐specific patterns of life‐history traits and their heritability. SNP data from adults returning from sea over a 14‐year period were used to identify 13,474 parent–offspring trios. These pedigrees were used to determine age structure, size distributions and family sizes for these fish, as well as to estimate the heritability of two key life‐history traits, spawn date and age at maturity (first reproduction). Spawn date was highly heritable ( h 2 = 0.73) and had a cross‐sex genetic correlation near unity. We provide the first estimate of heritability for age at maturity in ocean‐going fish from this species and found it to be highly heritable ( h 2 from 0.29 to 0.62, depending on sex and method), with a much lower genetic correlation across sexes. We also evaluated genotypes at a migration‐associated inversion polymorphism and found sex‐specific correlations with age at maturity. The significant heritability of these two key reproductive traits in these imperiled fish, and their patterns of inheritance in the two sexes, is consistent with predictions of both natural and sexually antagonistic selection (sexes experience opposing selection pressures). This emphasizes the importance of anthropogenic factors, including hatchery practices and ecosystem modifications, in shaping the fitness of this species, thus providing important guidance for management and conservation efforts.

Decadal impacts of wildfire fuel reduction treatments on ecosystem characteristics and fire behavior in alaskan boreal forests - Melissa A. Boyd; Xanthe J. Walker; Jennifer Barnes; Gerardo Celis; Scott J. Goetz; Jill F. Johnstone; Nicholas T. Link; April M. Melvin; Lisa Saperstein; Edward A.G. Schuur; Michelle C. Mack (Forest Ecology and Management, 2023)

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget - Jennifer D. Watts; Mary Farina; John S. Kimball; Luke D. Schiferl; Zhihua Liu; Kyle A. Arndt; Donatella Zona; Ashley Ballantyne; Eugénie S. Euskirchen; Frans‐Jan W. Parmentier; Manuel Helbig; Oliver Sonnentag; et al. (Global Change Biology, 2023)
Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration ( R eco ), net ecosystem CO 2 exchange (NEE; R eco − GPP), and terrestrial methane (CH 4 ) emissions for the Arctic‐boreal zone using a satellite data‐driven process‐model for northern ecosystems (TCFM‐Arctic), calibrated and evaluated using measurements from >60 tower eddy covariance (EC) sites. We used TCFM‐Arctic to obtain daily 1‐km 2 flux estimates and annual carbon budgets for the pan‐Arctic‐boreal region. Across the domain, the model indicated an overall average NEE sink of −850 Tg CO 2 ‐C year −1 . Eurasian boreal zones, especially those in Siberia, contributed to a majority of the net sink. In contrast, the tundra biome was relatively carbon neutral (ranging from small sink to source). Regional CH 4 emissions from tundra and boreal wetlands (not accounting for aquatic CH 4 ) were estimated at 35 Tg CH 4 ‐C year −1 . Accounting for additional emissions from open water aquatic bodies and from fire, using available estimates from the literature, reduced the total regional NEE sink by 21% and shifted many far northern tundra landscapes, and some boreal forests, to a net carbon source. This assessment, based on in situ observations and models, improves our understanding of the high‐latitude carbon status and also indicates a continued need for integrated site‐to‐regional assessments to monitor the vulnerability of these ecosystems to climate change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The timing of anadromous bull trout migrations in estuarine and marine waters of Puget Sound, Washington - F. A. Goetz; E. Beamer; E. J. Connor; E. Jeanes; C. Kinsel; J. W. Chamberlin; C. Morello; T. P. Quinn (Environmental Biology of Fishes, 2021)

Testing for hybridisation of the Critically Endangered Iguana delicatissima on Anguilla to inform conservation efforts - Kieran C. Pounder; F. Mukhida; R. P. Brown; D. Carter; J. C. Daltry; T. Fleming; M. Goetz; L. G. Halsey; G. Hughes; K. Questel; I. J. Saccheri; R. Williams; et al. (Conservation Genetics, 2020)
The Caribbean Island of Anguilla in the north-eastern Lesser Antilles is home to one of the last populations of the Critically Endangered Lesser Antillean iguana Iguana delicatissima . This population is highly threatened primarily because of hybridisation with non-native Iguana iguana . This study assesses the degree of hybridisation between Anguilla’s Iguana species firstly using morphological characteristics and then genetic analysis to validate the genetic integrity of morphologically identified I. delicatissima . We also examined the genetic diversity of Anguilla’s I. delicatissima population, and that of a population on the nearby island of Îlet Fourchue, St Barthélemy. Forty-five iguanas were captured in Anguilla and 10 in St Barthélemy, and sequences from 3 nuclear and 1 mtDNA genes were obtained for each. Of the 45 iguanas captured in Anguilla, 22 were morphologically identified as I. delicatissima , 12 as I. iguana and the remainder were identified as hybrids. Morphological assignments were all confirmed by genetic analyses except for one I. iguana and one hybrid individual. These two individuals appeared likely to have originated following ancestral hybridisation events several generations ago. A significant paucity of genetic diversity was found within Anguillan and St Barthélemy I. delicatissima populations, with a single haplotype being identified for each of the three nuclear genes and the mtDNA sequence. This study highlights the urgency for immediate action to conserve Anguilla’s remnant I. delicatissima population. Protection from hybridisation will require translocation to I. iguana -free offshore cays, with supplementary individuals being sourced from neighbouring islands to enhance the genetic diversity of the population.

Climate change decreases the cooling effect from postfire albedo in boreal North America - Stefano Potter; Kylen Solvik; Angela Erb; Scott J. Goetz; Jill F. Johnstone; Michelle C. Mack; James T. Randerson; Miguel O. Román; Crystal L. Schaaf; Merritt R. Turetsky; Sander Veraverbeke; Xanthe J. Walker; et al. (Global Change Biology, 2020)
Fire is a primary disturbance in boreal forests and generates both positive and negative climate forcings. The influence of fire on surface albedo is a predominantly negative forcing in boreal forests, and one of the strongest overall, due to increased snow exposure in the winter and spring months. Albedo forcings are spatially and temporally heterogeneous and depend on a variety of factors related to soils, topography, climate, land cover/vegetation type, successional dynamics, time since fire, season, and fire severity. However, how these variables interact to influence albedo is not well understood, and quantifying these relationships and predicting postfire albedo becomes increasingly important as the climate changes and management frameworks evolve to consider climate impacts. Here we developed a MODIS‐derived ‘blue sky’ albedo product and a novel machine learning modeling framework to predict fire‐driven changes in albedo under historical and future climate scenarios across boreal North America. Converted to radiative forcing (RF), we estimated that fires generate an annual mean cooling of −1.77 ± 1.35 W/m 2 from albedo under historical climate conditions (1971–2000) integrated over 70 years postfire. Increasing postfire albedo along a south–north climatic gradient was offset by a nearly opposite gradient in solar insolation, such that large‐scale spatial patterns in RF were minimal. Our models suggest that climate change will lead to decreases in mean annual postfire albedo, and hence a decreasing strength of the negative RF, a trend dominated by decreased snow cover in spring months. Considering the range of future climate scenarios and model uncertainties, we estimate that for fires burning in the current era (2016) the cooling effect from long‐term postfire albedo will be reduced by 15%–28% due to climate change.

Structure of cocoa farming systems in West and Central Africa: a review - Denis J. Sonwa; Stephan F. Weise; Goetz Schroth; Marc J. J. Janssens; Howard-Yana Shapiro (Agroforestry Systems, 2019)

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

Species and Genotype Effects of Bioenergy Crops on Root Production, Carbon and Nitrogen in Temperate Agricultural Soil - Andrew S. Gregory; Jennifer A. J. Dungait; Ian F. Shield; William J. Macalpine; Jennifer Cunniff; Mark Durenkamp; Rodger P. White; Adrian Joynes; Goetz M. Richter (BioEnergy Research, 2018)

Dimethylsulfoniopropionate (DMSP) Increases Survival of Larval Sablefish, Anoplopoma fimbria - Jonathan S. F. Lee; Rachel S. Poretsky; Matthew A. Cook; Jose J. Reyes-Tomassini; Barry A. Berejikian; Frederick W. Goetz (Journal of Chemical Ecology, 2016)

Diversity of movements by individual anadromous coastal cutthroat trout Oncorhynchus clarkii clarkii - F. A. Goetz; B. Baker; T. Buehrens; T. P. Quinn (Journal of Fish Biology, 2013)
Wild, downstream‐migrating cutthroat trout, Oncorhynchus clarkii clarkii , smolts and adults were captured at a weir in Big Beef Creek, Hood Canal, Washington, surgically implanted with acoustic tags and tracked to identify spring and summer movements using stationary receivers in order to test the assumption that the species moves little while in marine waters. Overall, 93–96% migrated from the stream into the east side of the long narrow fjord, where they dispersed north and south along the shoreline. Most O. c. clarkii were detected nearshore within 10 km of the release site, with declining detection rates to 77 km. Over one‐third (36%) crossed c . 2–4 km of deep water to the other side but only one O. c. clarkii left the Hood Canal basin. Movements and behaviour patterns did not differ between smolts and adults but cluster analysis revealed two modes of distribution, here categorized as residents and migrants. Within these categories of overall distribution, a range of finer‐scale behaviour patterns was observed, including sedentary individuals, daily moving between proximate sites and more continuous long‐distance travel. Diel movement patterns varied markedly among individuals but overall activity increased near dawn, peaked around mid‐day and declined but continued at night. These patterns contrast with sympatric and closely related steelhead trout, Oncorhynchus mykiss , providing new insights into the diversity of salmonid behaviour.

Comparative susceptibility among three stocks of yellow perch, P erca flavescens ( M itchill), to viral haemorrhagic septicaemia virus strain IV b from the G reat L akes - W Olson; E Emmenegger; J Glenn; J Winton; F Goetz (Journal of Fish Diseases, 2013)
The G reat L akes strain of viral haemorrhagic septicaemia virus IV b ( VHSV ‐ IV b) is capable of infecting a wide number of naive species and has been associated with large fish kills in the Midwestern U nited S tates since its discovery in 2005. The yellow perch, P erca flavescens ( M itchill), a freshwater species commonly found throughout inland waters of the United States and prized for its high value in sport and commercial fisheries, is a species documented in several fish kills affiliated with VHS . In the present study, differences in survival after infection with VHSV IV b were observed among juvenile fish from three yellow perch broodstocks that were originally derived from distinct wild populations, suggesting innate differences in susceptibility due to genetic variance. While all three stocks were susceptible upon waterborne exposure to VHS virus infection, fish derived from the M idwest (Lake Winnebago, WI ) showed significantly lower cumulative % survival compared with two perch stocks derived from the East Coast ( P erquimans River, NC and C hoptank River, MD ) of the U nited S tates. However, despite differences in apparent susceptibility, clinical signs did not vary between stocks and included moderate‐to‐severe haemorrhages at the pelvic and pectoral fin bases and exophthalmia. After the 28‐day challenge was complete, VHS virus was analysed in subsets of whole fish that had either survived or succumbed to the infection using both plaque assay and quantitative PCR methodologies. A direct correlation was identified between the two methods, suggesting the potential for both methods to be used to detect virus in a research setting.

Guppies as heterospecific facilitators: a precursor of exploratory behavior? - Douglas F. Fraser; Christopher J. Brousseau; Kristina L. Cohen; Summer A. Morse-Goetz (Behavioral Ecology and Sociobiology, 2011)

Characterization of a highly inducible novel CC chemokine from differentiated rainbow trout (Oncorhynchus mykiss) macrophages - S. MacKenzie; C. Liarte; D. Iliev; J. V. Planas; L. Tort; F. W. Goetz (Immunogenetics, 2004)

Response of Nebraska Sand Hills Natural Vegetation to Drought, Fire, Grazing, and Plant Functional Type Shifts as Simulated by the Century Model - Jennifer M. Mangan; Jonathan T. Overpeck; Robert S. Webb; Carol Wessman; Alexander F. H. Goetz (Climatic Change, 2004)

Targeting Microparticles to Select Tissue via Radiation-Induced Upregulation of Endothelial Cell Adhesion Molecules - Mohammad F. Kiani; Hong Yuan; Xin Chen; Lee Smith; M. Waleed Gaber; Douglas J. Goetz (Pharmaceutical Research, 2002)

Chaunopycnis pustulata sp. nov., a new clavicipitalean anamorph producing metabolites that modulate potassium ion channels - Gerald F. Bills; Jon D. Polishook; Michael A. Goetz; Raymond F. Sullivan; James F. White (Mycological Progress, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Molecular characterization and sequencing of antifreeze proteins from larvae of the beetle Dendroides canadensis - J. G. Duman; N. Li; D. Verleye; F. W. Goetz; D. W. Wu; C. A. Andorfer; T. Benjamin; D. C. Parmelee (Journal of Comparative Physiology B, 1998)